(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Thyroid nodules are commonly encountered in clinical practice. Differentiating between benign and malignant lesions is crucial for proper treatment. Ultrasonography with TIRADS classification helps stratify the risk. This study aims to assess TIRADS’ accuracy in distinguishing between benign and malignant thyroid nodules by validating it against histopathological findings. Methodology: A cross-sectional study was conducted at CMH Muzaffarabad from September 19, 2023, to March 18, 2024, involving 153 patients with thyroid nodules. Ultrasonography with ACR-TIRADS scoring by a radiologist classified nodules as benign or malignant. Histopathological analysis of thyroidectomy specimens served as the reference standard for evaluating TIRADS diagnostic performance. Parameters assessed included sensitivity, specificity, PPV, NPV, and accuracy. Results: In a study with 153 patients, 56.2% were male and 43.8% were female, with a mean age of 53.3 ± 10.75 years. The mean nodule size was 2.5 ± 1.3 cm. Histopathology confirmed 69.9% malignant and 30.1% benign lesions. Ultrasonography detected 62.1% malignant and 37.9% benign nodules. Ultrasonography showed a sensitivity of 85.9%, specificity of 93.4%, PPV of 96.8%, NPV of 74.1%, and overall accuracy of 88.2% in distinguishing between benign and malignant lesions. Conclusion: The ACR-TIRADS scoring system in ultrasound is highly sensitive and specific in distinguishing between benign and malignant thyroid nodules. This non-invasive tool reliably guides clinical decisions, minimizing unnecessary invasive procedures. However, for conclusive diagnosis in suspicious cases, histopathological confirmation is still necessary.